Colloquial Language Use in Public Informational Signs - Ni Ketut Alit Ida Setianingsih; Ketut Santi Indriani (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
The presence of colloquial expressions in public signage commonly referred to ba- hasa gaul has increasingly become a linguistic hallmark in various tourism and recreational ar- eas in Indonesia. This study investigates the use of informal language on public signage at Pantai Kelan, Bali, and analyzes such linguistic choices that reflect social dynamics, youth identity, and evolving modes of communication in public space. Grounded in sociolinguistic perspectives, the research highlights the role of signage as not only a medium of information, but also a space for constructing shared meaning and fostering engagement through culturally resonant expressions. This qualitative research employed observational and documentation methods. It focused on twelve public signs installed at Pantai Kelan. Data were collected through field observations, photographic documentation, and subsequent transcription and analysis of the linguistic forms. The analysis fo- cused on identifying dominant lexical patterns, stylistic choices, and communicative functions of the language used. The signs were then interpreted with reference to their potential cultural, social, and interactional implications within the broader framework of linguistic landscape studies. The findings indicate that the use of bahasa gaul in signage serves multiple purposes: capturing atten- tion, expressing local identity, evoking humor, and connecting with a predominantly young and digital-native audience. Rather than being perceived as informal or inappropriate, such language use contributes to the effectiveness of public communication in specific contexts. The study con- tributes to the growing body of literature on language in public space and emphasizes the impor- tance of cultural relevance and sociolinguistic awareness in designing public signage that is both meaningful and impactful